STUDY OF THE CRATERS OF THE MOON OBSERVED FROM NATIONAL OBSERVATORY NAGARKOT, NEPAL - Parajuli, P; Dhungel, P R; Khanal, U; Shahi, S R (Scientific World, 2015)
We studied the craters of the satellite Moon using images taken from National Observatory located at Nagarkot, Bhaktapur, Nepal during the period from November 8, 2012 to January 14, 2014. We captured the images of the crater of the Moon using Meade 16-inch LX200GPS Schmidt-Cassegrain telescope. The images were processed in the software ALADIN 2.5. To measure the distance, we drew lines across the craters, and took the lengths of those lines using ALADIN 2.5 software in terms of pixel size. Using the pixel size of the image from the software, we obtained the diameter of the craters under study. This work includes the measured diameters of eight different craters of Moon, and their comparison with the published results. Our findings on the diameter of the craters of moon is in close agreement with the published values. Scientific World, Vol. 12, No. 12, September 2014, page 9-13